Réponses

2014-01-04T14:15:52+01:00
Bonjour

A = 7(5a -9) = 35a - 56

B = (8b -4)(5 +3b) = 40b + 24b² -20 -12b = 24b² + 28b -20

C = 2c(-3c +9) = - 6c² + 18c

D = (5d +6) - ( 3d -4) = 5d +6 -3d +4 = 2d +10

E = 3(4x-5) +8(3 +2x) = 12x -15 + 24 + 16x = 28x + 9

F = 8((6x -3) - 4(12x+5) = 48x - 24 - 48x - 20 = -44

C = (3x-1)² -4x (3x-1)
C = 9x² - 6x +1 - 12x² +4x
C = -3x² -2x +1
Pour x = 0
C = 1
Pour x = √2
C = -12 - 2√2 +1
C = -11 -2√2

Factorisation
C = (3x-1)(3x-1) - 4x
C = (3x-1)(3x-1-4x)
c = (3x-1)(-x -1)

(3x-1)x+1) = 0
soit 3x-1 = 0 donc 3x = 1 et x = 1/3
soit x+1 = 0 et x = -1

A = (x-2)² +(x-2)(3x+1)
A = x² -4x +4 + 3x² +x - 6x -2
A = 4x² -9x +2

A = (x-2)(x-2) + (3x +1)
A = (x-2)(x-2 +3x +1)
a = (x-2)( 4x -1)
(x-2)(4x-1) = 0
soit x-2 = 0 et x =2
soit 4x-1 = 0 donc 4x = 1 et x = 1/4

Pour x = 1/2
A = (1/2 -2) ( 4/2 -1)
A = ( 1/2 - 4/2)(4/2 - 2/2)
A = (-3/2)( 2/2)
a = - 6/4 = - 3/2